2012
DOI: 10.1128/jcm.00508-12
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Streptococcus pneumoniae from Nonpneumococcal Streptococci of the Streptococcus mitis Group by Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry

Abstract: The differentiation of species within the Streptococcus mitis group has posed a problem in the routine diagnostic microbiology laboratory for some time. It also constitutes a major weakness of recently introduced matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) fingerprinting systems. As the phylogenetic resolution of the spectral similarity measures employed by these systems is insufficient to reliably distinguish between the most closely rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 26 publications
4
58
0
1
Order By: Relevance
“…and Anaerococcus spp.). However, while MALDI-TOF MS has a reported reliability of >95% (of routine isolates grown on solid media in the laboratory), 19 its limitations include inability to differentiate genetically similar organisms, such as Streptococcus pneumoniae from other members of the Streptococcus mitis group, 20 and Shigella species from Eschericheria coli. 21 Despite this, MALDI-TOF MS analysis can reduce manual workload for medical scientists and improve throughput of laboratory samples.…”
Section: Can Laboratory Results Be Expedited?mentioning
confidence: 99%
“…and Anaerococcus spp.). However, while MALDI-TOF MS has a reported reliability of >95% (of routine isolates grown on solid media in the laboratory), 19 its limitations include inability to differentiate genetically similar organisms, such as Streptococcus pneumoniae from other members of the Streptococcus mitis group, 20 and Shigella species from Eschericheria coli. 21 Despite this, MALDI-TOF MS analysis can reduce manual workload for medical scientists and improve throughput of laboratory samples.…”
Section: Can Laboratory Results Be Expedited?mentioning
confidence: 99%
“…1,7,18,21,22 For instance, it has recently been reported that improvements to the database enable a more reliable distinction between S. pneumoniae and viridans group streptococci. 23,24 Because the reference databases are not static and expanded regularly to fill in current gaps in identification, updates will continue to improve the performance of MALDI-TOF MS. 18 To the best of our knowledge, this study represents the first implementation and use of MALDI-TOF MS for the identification of bacteria and fungi in a hospital in tropical Africa. MALDI-TOF MS has previously been implemented and used for research purposes in South Africa for protein identification and bacterial identification, but its use was restricted to a few bacterial species in environmental studies of plant pathology or river water.…”
Section: Discussionmentioning
confidence: 99%
“…93 One of MALDI-TOF MS drawbacks is that it exhibits reduced sensitivity for Gram-positive bacteria and polymicrobial infections with respect to conventional approaches; for example, it is not able to identify different species of the S. viridans group. 94 Furthermore, this proteomic technology cannot be applied directly to whole blood; a subculture is necessary. …”
Section: Maldi-tof Msmentioning
confidence: 99%